Synthesis and Biological Activity of Some Substituted 2-Phenyl-quinazolin-4-ones - Raghavendra, N.M.; Niranjan, M.S.; Venkatesh, P.; Prashantha Kumar, B.R.; B. Gowda, Narendra; Sripathi, M.S. (Asian Journal of Chemistry, 2016)
Synthesis of nine 2,3,6-trisubstituted quinazolin-4-ones is reported. The nine compounds contain a bromine atom at position 6, a phenyl group at position 2 while at position 3, one compound has free amino group and the remaining eight compounds have substituted benzalamino group. The synthesized compounds were screened for their anticancerous activity by evaluating the percentage increase in life span in mice bearing Ehrlich ascites carcinoma at different dose, viz., 2, 50, 100 and 250 µg/mouse/day on alternate days for a total period of 10 days. Synthesized compounds were also investigated for their antimicrobial activity against two gram +ve and two gram -ve microorganisms using agar cup diffusion method.